The psychological resilience of teenagers in terms of their everyday emotional balance and the impact of emotion regulation strategies - Yu, Zengyan; Liu, Wen (Frontiers in Psychology, 2025)
Abstract Objective: Adolescents are also more vulnerable to the effects of everyday life stimuli and exhibit a range of negative emotional states that can develop into severe affective disorders. However, Psychological resilience maybe enable the prevention of emotional problems associated with daily stress rather than intervening treating the problem after it has occurred. Methods: A total of 104 individuals (54 participants in the high psychological resilience group and 50 participants in the low psychological resilience group) were first identified. Then, the 8-day experiential sampling method was used to determine the characteristics of adolescents with different psychological resilience levels in terms of emotional balance under daily stress. Further combined with diary method research, a multilayered linear model was used to explore the predictive effects of six emotion regulation strategies on adolescents' emotional balance. Results: The obtained Results show that high psychological resilience adolescents demonstrated higher levels of emotional balance and positive rates and lower rates of change in emotional balance than low psychological resilience adolescents. In terms of facilitating emotion regulation strategies, high psychological resilience was associated with greater use of cognitive reappraisal and social sharing strategies (which positively predicted emotional balance under daily stress) and less use of expression suppression and rumination strategies (which negatively predicted levels of emotional balance). These findings support that adolescents with high psychological resilience exhibit good adaptive emotional states in daily stressful situations, which is closely related to their use of adaptive emotion regulation strategies and may be useful for further intervention research. Conclusions: Adolescents with high psychological resilience exhibit good adaptive emotional states in daily stressful situations, which is closely related to their use of adaptive emotion regulation strategies such as cognitive reappraisal and social sharing and may be useful for further intervention research.